2021
DOI: 10.1007/s10980-021-01287-7
|View full text |Cite
|
Sign up to set email alerts
|

Using landscape metrics to characterize towns along an urban-rural gradient

Abstract: Context Urban-rural gradients are useful tools when examining the influence of human disturbances on ecological, social and coupled systems, yet the most commonly used gradient definitions are based on single broad measures such as housing density or percent forest cover that fail to capture landscape patterns important for conservation. Objectives We present an approach to defining urban–rural gradients that integrates multiple landscape pattern metrics r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Additionally, urban and agricultural land cover in Maine contain different bee species than found in the forested matrix (Du Clos et al 2020; see also Harrison et al 2018), contributing to the greater species richness we observed in power line corridors in the Midcoast growing region. Urban land cover in Maine's lowbush blueberry production landscape is generally classi ed as exurban along an urban-rural land use gradient (Kaminski et al 2021), meaning there is plenty of green space and natural area that provides bee habitat. Although we found more wetland land cover Downeast than Midcoast, we do not have evidence that wetlands in uence Maine bee communities (Du Clos et al 2020).…”
Section: Landscape Context and Mass-owering Cropsmentioning
confidence: 99%
“…Additionally, urban and agricultural land cover in Maine contain different bee species than found in the forested matrix (Du Clos et al 2020; see also Harrison et al 2018), contributing to the greater species richness we observed in power line corridors in the Midcoast growing region. Urban land cover in Maine's lowbush blueberry production landscape is generally classi ed as exurban along an urban-rural land use gradient (Kaminski et al 2021), meaning there is plenty of green space and natural area that provides bee habitat. Although we found more wetland land cover Downeast than Midcoast, we do not have evidence that wetlands in uence Maine bee communities (Du Clos et al 2020).…”
Section: Landscape Context and Mass-owering Cropsmentioning
confidence: 99%
“…As researchers increasingly turn to R, a new 'landscapemetrics' package, an extensive collection of widely used LM becomes more popular [16]. In recent decades, interpreting these metrics has become an important research topic in landscape ecology [17], as well as in relation to the cityscape [18], sustainable development [19], the monitoring of land cover changes [20][21][22], and urban or regional planning [23]. Recent research has also shown the need to emphasize multi-scale interactions in landscape pattern studies, suggesting methods for big data analysis [24].…”
Section: Introductionmentioning
confidence: 99%
“…Landscape metrics, otherwise referred to as spatial metrics, is a very useful tool for quantifying and assessing the distribution, pattern and structure of land use and land cover (Li & Wu, 2004;Kaminski et al, 2021;Maselli & Negri, 2021;Mohammadreza et al, 2022). The focus of landscape metrics is usually on three major characteristics of landscape: structure, function and change (Mohammadreza et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Different types of landscape metrics have been identified and applied to quantify and assess landscape fragmentation, both at level and class levels (McGarigal & Marks, 1995;Singh et al, 2017;Hesselbarth et al, 2019;Das & Angadi, 2021;Ai et al, 2022). Urban landscape fragmentation is usually the consequence of changes in landscape structure (Simons, 1988;Li & Wu, 2004;Kaminski et al, 2021). These changes are by-products of decreasing heterogeneity of landscape compositions and profound landscape fragmentation (Hartvigsen, 2014;Singh et al, 2014;Ciaian et al, 2018;Olayiwola & Fakayode, 2019;Bertram et al, 2021;Abbas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%